Internet search, fund flows, and fund performance - Chen, Hong-Yi; Chen, Hsuan-Chi; Lai, Christine W. (Journal of Banking & Finance, 2021)
This study uses the Google search volume index as a direct measure of investor attention to explore the connection between attention-grabbing information and fund flows, future performance, and the survivorship of newly issued funds. We find that investors often engage in attention-driven purchases of new funds that have captured their attention online. However, fund investors who conduct internet searches and make attention-driven purchases are less sophisticated and fail to allocate their capital for earning abnormal returns. We also find that attention-induced inflows can help sustain new funds in competitive fund markets via potential mitigation of mergers and liquidations. Our robustness checks show similar results for old funds, but attention-driven fund flows do not enhance the survival of old funds.